Lack of transparency and social participation undermine the fight against deforestation in Brazil - Carvalho, Raquel; G. Coelho-Junior, Marcondes; Valdiones, Ana Paula; Silgueiro, Vinicius; Thuault, Alice (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
The Brazilian government wrapped up 2021 with a masquerade at COP26 (26th UN Climate Change Conference of the Parties): hiding PRODES (the annual Amazon deforestation report). After three years of denying and dismantling the public apparatus to fight Amazon deforestation, this is emblematic of how transparency and social participation have been neglected. Transparency of PRODES has been crucial to all initiatives against deforestation. Notwithstanding, the Brazilian government has not only worked to discredit PRODES, but limited access to other environmental data and decreed a ‘gag law’. Responses to requests of public data are largely unsatisfactory and information on deforestation permits (key to understanding the extent of legal and illegal deforestation) is either missing or incomplete. Social participation has been strongly limited after one-fifth of 22 national boards monitoring the public administration was extinct and almost half restructured. As an outcome, the Amazon Fund, the most important source of financial support against deforestation, was frozen. These systemic problems compromise the political struggle to combat Amazon deforestation and worsen the living conditions of those peoples protecting forests. Increasing transparency of environmental data through robust and reliable mechanisms, and ensuring social participation in the decision-making processes are crucial to halt deforestation and support Brazil’s role as an international player.